A Systematic review and meta analysis of estrogen receptor beta as a predictive factor in breast cancer patients - Armansyah Maulana Harahap; Kurnia Agustini; Sri Ningsih (International Journal of Ecophysiology, 2023)
It is unclear how estrogen receptor beta (ER) affects prognosis in breast cancer that is in the early stages. To determine the predictive value of ER in patients with early-stage breast cancer, we conducted a systematic review and meta-analysis. We looked for studies that evaluated the ER status in breast cancer patients article between 2010 and 2018 by searching Medline, Embase, and the Web of Science. 1700 participants from 18 studies total who met our inclusion and exclusion criteria were included. A Technical Expert Panel (TEP) of 3 medical specialist and expertise of disorder the abnormally cell cycle and cancer performed the review using the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) model. The TEP planned a research on PubMed selecting “cancer” and “Breast Cancer” as MeSH (Medical Subject Headings) term adding to PubMed Search Builder the terms “Estrogen” and “Estrogen receptor”. TEP is considered for eligibility articles published within the last 13 years, including original research, in particular in vitro studies, and animal and clinical studies in English. Results: Of the 90 identified studies, TEP included 15 studies, 8 Systematical Review, and 4 clinical studies and 3 Review report. Our scoping review describes and summarizes the important develop highly selective anti-ERÎ² antibodies that are applied to large well characterized human breast cancer samples to validate their diagnostic potential and to explore ERÎ²-selective agonists in animal models of breast cancer to validate their therapeutic potential